Український метанаратив в епоху пропаґанди - Горенко, О.М. (Український історичний журнал, 2014)
Розглядаються концептуальні й понятійно-термінологічні особливості метанаративу як методу. Акцентується необхідність посилення комунікативного потенціалу українського ґранд-наративу. The article broaches conceptual and notional-terminological peculiarities of metanarrative
as method. The necessity to enhance communicative potential of Ukrainian
grand-narrative is also accentuated here.